When Colleges Sang : The Story of Singing in American College Life - Winstead, James Lloyd (Book collections on Project MUSE., 2013)
This book is an illustrated history of the rich culture of college singing from the earliest days of the American republic to the early twenty-first century. Before fraternity songs, alma maters, and the rahs of college fight songs became commonplace, students sang. Students in the earliest American colleges created their own literary melodies that they shared with their classmates. College singing expanded in conjunction with the growth of the nation and the American higher education system. While it was often simply an entertaining pastime, singing had other subtle and not-so-subtle effects. Singing indoctrinated students into the life of formal and informal student organizations as well as encouraged them to conform to college rituals and celebrations. University faculty used songs to reinforce the religious practices and ceremonial observances that their universities supported. Students used singing for more social purposes: they sang to praise their peer's achievements (and underachievements), mock the faculty, and provide humor. In extreme circumstances, they sang to intimidate classmates and faculty, and to defy college authorities. Singing was, and still is, an intrinsic part of campus culture.